La protection de la maternité au travail. Révision de la convention (n°103) (révisée), et de la recommandation (n°95) sur la protection de la maternité, 1952. Rapport V (2) (Genève, 1999)
"Presents replies received and commentaries from the member states for the revision of the Maternity Protection Convention (Revised), 1952 (No.103), and Recommendation, 1952 (No.95). Includes proposed conclusions."